Industrial water consumption efficiency and driving factors based on the super-efficient SBM and Tobit approach - Haixia Duo; Ning Wang; Yunfeng Qiao; Zhao Li; Guang Yang; Hongguang Liu; Gang Chen; Fadong Li (Scientific Reports)
Abstract Water scarcity in arid regions is a significant factor constraining industrial development globally. Xinjiang, which has a huge potential for economic development, is constrained for its local industry development owing to the scarcity of water resources. Enhancing the efficiency of industrial water consumption is thus crucial to alleviate the conflict between water resource constrain and economic development. This study investigated the industrial water consumption efficiency in the economic zone of the northern slope of the Tianshan Mountains (EZNSTM) of Xinjiang from 2001 to 2020. The super-efficient SBM and Tobit model were used to identify the key drivers of regional industrial water consumption efficiency. Factors including economic development, government influence, industrial structure, and urbanization levels were found to affect the overall industrial water consumption efficiency. On the contrary, being open to the outside world and natural resource endowment did not significantly impact the water consumption efficiency. This paper identified the disparities in industrial water use and consumption efficiency across different regions of the EZNSTM and elucidated the primary factors influencing industrial water consumption efficiency in the area, which provided a critical foundation for coordinating future economic development and water resource utilization.